2010
DOI: 10.1007/s00268-010-0683-1
|View full text |Cite
|
Sign up to set email alerts
|

Is Breast Cancer the Same Disease in Asian and Western Countries?

Abstract: A mini-symposium was held in Montreal, Canada, at the International Surgical Week for the Breast Surgical International in 2007 addressing the question whether breast cancer is the same disease in Asian and Western countries. Numerous investigators from Asian and Western countries presented the epidemiologic and clinical outcome data of women with breast cancer. Although there are significant similarities, the striking difference is that the peak age for breast cancer is between 40 and 50 years in the Asian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
395
11
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(458 citation statements)
references
References 92 publications
(100 reference statements)
36
395
11
2
Order By: Relevance
“…For instance, the peak age of female breast cancer onset is approximately 40 years in Asian countries, while it is about 60 years in Western countries (Green et al, 2008). This difference may be associated with many factors, including regional disparity, ethnic background, genetic background, lifestyle, dietary patterns, economic level, and overall education level (Leong et al, 2010). Therefore, studies on female breast cancer in Western countries may not be relevant to female breast cancer in Asian countries, such as China.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the peak age of female breast cancer onset is approximately 40 years in Asian countries, while it is about 60 years in Western countries (Green et al, 2008). This difference may be associated with many factors, including regional disparity, ethnic background, genetic background, lifestyle, dietary patterns, economic level, and overall education level (Leong et al, 2010). Therefore, studies on female breast cancer in Western countries may not be relevant to female breast cancer in Asian countries, such as China.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence-age curves of breast cancer around the world are significantly different. In China and Japan, the peak age of breast cancer incidence is about 40-50 years and cancer incidence is associated with increased mortality, while in the United States and other western countries, the incidence continuously increases with age and the morality rate is decreasing [3,12,13]. The underlying reasons for the different incidence-age curves are not clear.…”
Section: Discussionmentioning
confidence: 92%
“…The average age at diagnosis of breast carcinoma in the US is 61 years [3,4]. It is to be noted that other studies from India too have reported similar mean ages at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…It is to be noted that other studies from India too have reported similar mean ages at presentation. [4] Young age at diagnosis has been found to be independently predictive of worse survival [5,6]. The youngest patient is 27 years old, and nearly half of the study population is in the premenopausal age group.…”
Section: Discussionmentioning
confidence: 99%